To rewrite \( \frac{1}{4^{-3}} \) without an exponent, you can use the property of exponents that states \( a^{-n} = \frac{1}{a^n} \).
Thus,
\[ \frac{1}{4^{-3}} = 4^{3} = 64. \]
So, the expression \( \frac{1}{4^{-3}} \) without an exponent is 64.
1/4^-3
1 answer
To rewrite \( \frac{1}{4^{-3}} \) without an exponent, you can use the property of exponents that states \( a^{-n} = \frac{1}{a^n} \).
Thus,
\[ \frac{1}{4^{-3}} = 4^{3} = 64. \]
So, the expression \( \frac{1}{4^{-3}} \) without an exponent is 64.